Following London's Footsteps - Implications for Structure and Reactivity - Rummel, Lars; Justus Liebig University Giessen (My University, 2022)
London dispersion interactions are ubiquitously present in molecular chemistry and govern molecular aggregation, recognition as well as chemical selectivity. Nevertheless, as attractive part of the van der Waals interactions, London dispersion is generally egarded as weak and negligible. This work emphasizes the tremendous impact London dispersion interactions have on structural stability as well as chemical reactivity by focusing on a combination of experimental and computational investigations. During this work, numerous novel molecules were prepared and analyzed with the main focus on qualifying and quantifying noncovalent interactions. The results of this work might eventually enable a target-oriented use of dispersion energy donors, e.g. in synthesis and catalysis, to generate novel molecular structures, exploit reaction mechanisms or simply rationalize selectivities. In the first publication, we computationally investigated the unexpected thermodynamic stability of hexaphenylethane derivatives with heavier tetrels comprising the central bond. By exploiting various energy decomposition methods, the source of stabilization was found in an ideal ratio of attractive London dispersion interactions and repulsive Pauli exchange repulsion. The second and third publication report an experimental and computational study on the effects of silyl groups on a molecular balance. While the second publication focuses on the steric size of such groups, the third one emphasizes the fine interplay between attractive London dispersion interactions and an entropic penalty due to increasing flexibility. In both publications, the cyclooctatetraene molecular balance was exploited. The fourth publication describes the role of London dispersion on the conformational landscape of thiourea. By utilizing dispersion energy donors the syn-syn conformer was generated. The combination of low-temperature nuclear magnetic resonance experiments and computational analyses allowed quantification of London dispersion interactions. While the first four publications focus on structural ramifications of London dispersion, the next two cover the impact of London dispersion on reactivity. The fifth publication describes a hydrochlorination reaction under thermodynamic control. London dispersion was found to be key to rationalize product ratio. The sixth project describes the impact of dispersion energy donors on a kinetically controlled reaction. We utilized the Johnson-Corey-Chaykovsky reaction to qualify and quantify the impact of London dispersion on transition states.
Keywords: noncovalent interactions; van der Waals forces; molecular balance; London dispersion interactions; ddc:540